Can the Full Spectrum Fitting Technique correctly detect Age Spreads in Young Star Clusters? - Asa'd, Randa (2019)
Integrated spectra of star clusters have proven to be accurate tools for obtaining age, metallicity and reddening of extragalactic clusters for which resolved data is not available. In this work we investigate the possibility of recovering age spreads of young star clusters (in the range log (age/year) 6.8 to 7.2) using full-spectrum fitting approach and provide the preliminary results using model spectral combinations, in order to examine whether this approach can be used for identifying age-spreads for a grid with combinations of S/N, cluster age and population mass fraction. Our preliminary results show that false age spreads might be obtained when fitting multiple ages using integrated spectra specially for the lower S/N. A more accurate experiment to determine how reliable is the recovery of the input parameters is needed.